2011
DOI: 10.1002/chem.201002101
|View full text |Cite
|
Sign up to set email alerts
|

Oligonuclear Ferrocene Amides: Mixed‐Valent Peptides and Potential Redox‐Switchable Foldamers

Abstract: Trinuclear ferrocene tris-amides were synthesized from an Fmoc- or Boc-protected ferrocene amino acid, and hydrogen-bonded zigzag conformations were determined by NMR spectroscopy, molecular modelling, and X-ray diffraction. In these ordered secondary structures orientation of the individual amide dipole moments approximately in the same direction results in a macrodipole moment similar to that of α-helices composed of α-amino acids. Unlike ordinary α-amino acids, the building blocks in these ferrocene amides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 77 publications
3
76
0
Order By: Relevance
“…In the crystal structure of diferrocene tBuO-CO-Fca-NH-Fc, however, three different conformations are observed for the Fca unit: the 1,1 0 rotamer without an intramolecular hydrogen bond; the 1,1 0 rotamer with an intramolecular hydrogen bond (sixmembered ring); and the 1,2 0 (1,5 0 ) rotamer with an eight-membered ring (see Scheme 21.1) [26]. This suggests only small energetic differences between possible conformers, and that intermolecular forces might well determine the conformation realized in the solid state.…”
Section: Systems With Amide-bridged Fca Unitsmentioning
confidence: 99%
“…In the crystal structure of diferrocene tBuO-CO-Fca-NH-Fc, however, three different conformations are observed for the Fca unit: the 1,1 0 rotamer without an intramolecular hydrogen bond; the 1,1 0 rotamer with an intramolecular hydrogen bond (sixmembered ring); and the 1,2 0 (1,5 0 ) rotamer with an eight-membered ring (see Scheme 21.1) [26]. This suggests only small energetic differences between possible conformers, and that intermolecular forces might well determine the conformation realized in the solid state.…”
Section: Systems With Amide-bridged Fca Unitsmentioning
confidence: 99%
“…Although used extensively in the field of sensors, [33][34][35] ferrocene has received little attention as an actuator of redox-dependent conformational switching [36]. Fc is slightly electron-donating [37,38] as compared to a phenyl group, which suggests that the H-bonded equilibrium will be biased away from the ferrocenyl amide (FcA) in the neutral state ("reduced", Figure 1).…”
Section: Open Accessmentioning
confidence: 99%
“…Having shown that putative switch 3 undergoes reversible oxidation, we attempted to use the [36,49]. They report that, while partial oxidation causes the Fc signals to broaden and shift downfield, other resonances belonging to protons further from the FcA group remain sharp.…”
Section: Characterizing the Redox Properties Of Switch 3 By Chemical mentioning
confidence: 99%
“…Peptide conformations of these oxidized species were also evaluated by DFT calculations. 9,56,57 Thus, arrangement of multiple redox-active metal complexes at appropriate positions of peptides would enable sequence-based multielectron functions in interconvertible folded structures. Figure 6.…”
Section: ç Redox-responsive Metallopeptidesmentioning
confidence: 99%